Sharing Humanity: Joan Slonczewski's Elysium Cycle. Issue 3 (1st December 2020) - Vanderbeke, Dirk
Abstract : In science fiction, the construction of alien life forms is usually less concerned with the exploration of the other than with reflections on the human condition and our status in evolving environments. Joan Slonczewski's Elysium Cycle is no exception to this rule, and its four novels discuss the question, "What does it mean to be human?" in ever new contexts. But instead of the action-driven plots that frequently structure tales of interstellar travel and colonization, we find a focus on negotiations between the different agents and representatives of alternate life forms to avoid escalating conflicts. Within these novels, the outbreak of large-scale violence can ultimately be prevented by compromise, but also by a willingness to recognize the similar in the other, the familiar in the non-human. This paper explores not only these aspects in Slonczewski's novels, but also her feminist and participatory epistemology as the basis for an alternative practice of science and politics.